Strategy for The Development of Pacu Jalur Tourism Objects In Increasing Regional Original Income - Nurman Nurman; Tri Yulastin; Zainal Zainal (International Journal of Economics Development Research (IJEDR), 2023)
The behavior of street vendors by making their own land causes the city's infrastructure to no longer function optimally and intact so that this becomes a problem. There are obstacles for the Kuantan Singingi Regency Tourism and Culture Office in realizing the development of Pacu Jalur tourism objects, the obstacle that greatly affects tourism development in Kuantan Singingi Regency is the limited funds owned by the Tourism and Culture Office. The lack of a budget from the government and the lack of third parties in investing have made the Kuantan Singingi Regency Tourism and Culture Office in realizing superior tourism destinations not optimal. The development strategy according to Cooper et al in Sunaryo (2013: 159) explains that: a. Tourist attraction objects which include uniqueness and attractions based on nature, culture and man-made/artificial. b. Accessibility which includes ease of transportation facilities and systems. c. Amenities which include tourism support and support facilities. d. Public facilities (Ancillary Services) that support tourism activities e. Institutions that have authority, responsibility and role in supporting the implementation of tourism activities. The type of research used is qualitative research with a descriptive approach, namely a type of research that aims to provide a systematic, factual and accurate description of the data in the field. This qualitative method will produce discoveries in the form of speech or writing and so on that support the research process. Qualitative descriptive research methods in this study were used to develop theories that were built from data obtained in the field.